2021
DOI: 10.1038/s41467-021-23240-7
|View full text |Cite
|
Sign up to set email alerts
|

Yap regulates skeletal muscle fatty acid oxidation and adiposity in metabolic disease

Abstract: Obesity is a major risk factor underlying the development of metabolic disease and a growing public health concern globally. Strategies to promote skeletal muscle metabolism can be effective to limit the progression of metabolic disease. Here, we demonstrate that the levels of the Hippo pathway transcriptional co-activator YAP are decreased in muscle biopsies from obese, insulin-resistant humans and mice. Targeted disruption of Yap in adult skeletal muscle resulted in incomplete oxidation of fatty acids and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…The infiltration of the adipose tissue by the pro-inflammatory immune cells such as classically activated (M1) macrophages, CD8+ and Th1 T cells and the reduced number of Treg cells further increase the production of inflammatory mediators [ 166 ]. Yap levels in the skeletal muscles of obese and insulin-resistant humans and animals were significantly lowered [ 167 ].…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The infiltration of the adipose tissue by the pro-inflammatory immune cells such as classically activated (M1) macrophages, CD8+ and Th1 T cells and the reduced number of Treg cells further increase the production of inflammatory mediators [ 166 ]. Yap levels in the skeletal muscles of obese and insulin-resistant humans and animals were significantly lowered [ 167 ].…”
Section: Obesitymentioning
confidence: 99%
“…Furthermore, it has been associated with inflammation and could damage muscle function and quality [ 26 , 199 , 201 ]. It was recently shown that inhibition of Yap impairs fatty acid oxidation and leads to lipotoxicity in skeletal muscle [ 167 ]. Type I fibers (slow-twitch oxidation fibers) collect more lipids with age in humans than type II fibers [ 202 ].…”
Section: Obesitymentioning
confidence: 99%
“…We then checked the effect of HSYA on lipogenesis and lipid oxidation, which showed that HSYA might elevate lipid utilization. Low-intensity exercise has been reported to induce a fuel selection switch from glucose to lipid, and intriguingly, this metabolic fuel strategy was enhanced in mice by HSYA treatment . As we all know, branched-chain amino acid utilization is also involved in fuel use during exercise, and a previous study showed that efficient branched-chain amino acid utilization contributes to high intrinsic exercise capacity and endurance capacity .…”
Section: Discussionmentioning
confidence: 97%
“…Low-intensity exercise has been reported to induce a fuel selection switch from glucose to lipid, and intriguingly, this metabolic fuel strategy was enhanced in mice by HSYA treatment. 43 As we all know, branched-chain amino acid utilization is also involved in fuel use during exercise, and a previous study showed that efficient branched-chain amino acid utilization contributes to high intrinsic exercise capacity and endurance capacity. 7 However, in this paper, we only studied the effect of HSYA on glucose utilization and fat utilization in skeletal muscle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The highly conserved Hippo pathway regulates several cellular processes. The main effectors of this pathway, Yap (Yes-Associated Protein) and Taz (Transcriptional co-activator with PDZ binding motif) are activated by exercise and interact with various signaling pathways to increase skeletal muscle size [ 161 , 162 , 163 , 164 , 165 ]. Muscles lacking Yap result in decreased muscle strength due to poor neuromuscular transmission, consistent with reduced AChR density and impaired clustering, reduced endplate occupancy, and reduced miniature endplate potential frequency [ 166 ].…”
Section: Exercisementioning
confidence: 99%